Membaca Sentimen #KaburAjaDulu dalam Lanskap Psikososial Gen Z pada Pendidikan Kewarganegaran - Sri Hadiningrum; Syuratty Astuti Rahayu Manalu (Jurnal Kawistara, 2025)
The hashtag #KaburAjaDulu reflects a psychosocial and ideological crisis among Indonesian Generation Z, especially in their relationship with the state and national identity. This study aims to examine how this phenomenon reveals a deep crisis of civic aspiration and the limitations of Citizenship Education (PPKn) in responding to young citizens’ emotional, psychological, and social realities. Utilizing a literature review approach supported by bibliometric analysis through VOSviewer, this study explores the dominant themes and research gaps across related academic publications. The findings indicate that health-related and migration discourses dominate the #KaburAjaDulu conversation, while the intersection with Citizenship Education and mental health remains weak. The novelty of this research lies in its critical synthesis using civic engagement and psychosocial resilience frameworks to propose a transformative model of PPKn that is context-sensitive, emotionally supportive, and socially empowering. The study recommends the integration of digital literacy, emotional education, and participatory pedagogy to strengthen national belonging and psychological well-being among young citizens.